Sirt1 overexpression protects murine osteoblasts against TNF-α-induced injury in vitro by suppressing the NF-κB signaling pathway - Huang, Wei (Nature Publishing Group, 2012)
AIM: Sirtuin 1 (Sirt1) is the class III histone/protein deacetylase that interferes with the NF-κB signaling pathway, thereby has anti-inflammatory function. This study was undertaken to investigate whether Sirt1 could protect osteoblasts against TNF-α-induced injury in vitro. METHODS: Murine osteoblastic cell line, MC3T3-E1, was used. Overexpress of Sirt1 protein in MC3T3-E1 cells was made by transfection the cells with Sirt1-overexpressing adenovirus. The levels of mRNAs and proteins were determined with qRT-PCR and Western blotting, respectively. The activity of NF-κB was examined using NF-κB luciferase assay. The NO concentration was measured using the Griess method. RESULTS: Treatment of MC3T3-E1 cells with TNF-α (2.5–10 ng/mL) suppressed Sirt1 protein expression in a concentration-dependent manner. TNF-α (5 ng/mL) resulted in an increase in apoptosis and a reduction in ALP activity in the cells. Overexpression of Sirt1 in the cells significantly attenuated TNF-α-induced injury through suppressing apoptosis, increasing ALP activity, and increasing the expression of Runx2 and osteocalcin mRNAs. Furthermore, overexpression of Sirt1 in the cells significantly suppressed TNF-α-induced NF-κB activation, followed by reducing the expression of iNOS and NO formation. Sirt1 activator resveratrol (10 μmol/L) mimicked the protection of the cells by Sirt1 overexpression against TNF-α-induced injury, which was reversed by the Sirt1 inhibitor EX-527 (5 μmol/L). CONCLUSION: Overexpression of Sirt1 protects MC3T3-E1 osteoblasts aganst TNF-α-induced cell injury in vitro, at least in part, via suppressing NF-κB signaling. Sirt1 may be a novel therapeutic target for treating rheumatoid arthritis-related bone loss.